Peningkatan Kompetensi Pedagogik Guru dalam Menyusun Perencanaan Pembelajaran Melalui Supervisi Akademik SDN Susukan 02 Semester I Tahun Pelajaran 2016/2017 - Y Andari (Universitas Sebelas Maret, 2019)
Abstract. The purpose of this study is to determine whether the teacher's Pedagogical competence in preparing learning plans can be improved through academic supervision. The results of this study are the teacher's pedagogical competence in preparing learning plans can be improved through academic supervision. The results of research on teacher competence in developing lesson plans that have increased in each cycle. In the pre-cycle stage, the teacher'sability to formulate learning goals only reached 48% and increased to 63% in the first cycle and 78% in the second cycle. The ability of teachers to determine learning material in the precycle stage is only 63% and has increased in the first cycle to 73% and 85% in the second cycle. The ability of teachers to determine learning strategies also increased from 53% in the pre-cycle stage to 68% in the first cycle and 83% in the second cycle. The ability of teachers to choose learning media is only 58% in the pre-cycle stage and has increased to 65% in the first cycle and 88% in the second cycle. While the ability of teachers in planning evaluation of learning has increased from 55% in the pre-cycle stage to 65% in the first cycle and 85% in the second cycle. So it can be concluded that academic supervision can improve the pedagogicalcompetence of teachers in preparing learning plans in SDN Susukan 02.